DNA Microarray and Signal Transduction Analysis in Pulmonary Artery Smooth Muscle Cells From Heritable and Idiopathic Pulmonary Arterial Hypertension Subjects. Issue 3 (March 2015) - Yu, Jun; Wilson, Jamie; Taylor, Linda; Polgar, Peter
Abstract Pulmonary arterial hypertension (PAH) is characterized by increased pulmonary vascular smooth muscle contraction and proliferation. Here, we analyze genome‐wide mRNA expression in human pulmonary arterial smooth muscle cells (HPASMC) isolated from three control, three hereditary (HPAH), and three idiopathic PAH (IPAH) subjects using the Affymetrix Human Gene ST 1.0 chip. The microarray analysis reveals the expression of 537 genes in HPAH and 1024 genes in IPAH changed compared with control HPASMC. Among those genes, 227 genes show similar directionality of expression in both HPAH and IPAH HPASMC. Ingenuity™ Pathway Analysis (IPA) suggests that many of those genes are involved in cellular growth/proliferation and cell cycle regulation and that signaling pathways such as the mitotic activators, polo‐like kinases, ATM signaling are activated under PAH conditions. Furthermore, the analysis demonstrates downregulated mRNA expression of certain vasoactive receptors such as bradykinin receptor B2 (BKB2R). Using real time PCR, we verified the downregulated BKB2R expression in the PAH cells. Bradykinin‐stimulated calcium influx is also decreased in PAH PASMC. IPA also identified transcriptional factors such p53 and Rb as downregulated, and FoxM1 and Myc as upregulated in both HPAH and IPAH HPASMC. The decreased level of phospho‐p53 in PAH cells was confirmed with a phospho‐protein array; and we experimentally show a dysregulated proliferation of both HPAH and IPAH PASMC. Together, the microarray experiments and bioinformatics analysis highlight an aberrant proliferation and cell cycle regulation in HPASMC from PAH subjects. These newly identified pathways may provide new targets for the treatment of both hereditary and idiopathic PAH. J. Cell. Biochem. 116: 386–397, 2015. © 2014 Wiley Periodicals, Inc.